2019
DOI: 10.1021/acssynbio.8b00364
|View full text |Cite
|
Sign up to set email alerts
|

Designing of a Cofactor Self-Sufficient Whole-Cell Biocatalyst System for Production of 1,2-Amino Alcohols from Epoxides

Abstract: Optically pure 1,2-amino alcohols are highly valuable products as intermediates for chiral pharmaceutical products. Here we designed an environmentally friendly non-natural biocatalytic cascade for efficient synthesis of 1,2-amino alcohols from cheaper epoxides. A redesignated ω-transaminase PAKω-TA was tested and showed good bioactivity at a lower pH than other reported transaminases. The cascade was efficiently constructed as a single one-pot E. coli recombinant, by coupling SpEH (epoxide hydrolase), MnADH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…NADH addition can obviously increase ( R )-(+)-perillyl alcohol yield ( Figure 4C ). Since NADH is costly, we integrated a NADH generating pathway, such as, formate dehydrogenase (FDH) for the regeneration of NADH ( Liu et al, 2019 ; Chen et al, 2021 ). FDH from Candida boidinii was expressed and strain 10 was constructed.…”
Section: Resultsmentioning
confidence: 99%
“…NADH addition can obviously increase ( R )-(+)-perillyl alcohol yield ( Figure 4C ). Since NADH is costly, we integrated a NADH generating pathway, such as, formate dehydrogenase (FDH) for the regeneration of NADH ( Liu et al, 2019 ; Chen et al, 2021 ). FDH from Candida boidinii was expressed and strain 10 was constructed.…”
Section: Resultsmentioning
confidence: 99%
“…Glutamine plays a pleiotropic role in cell function, contributing to processes such as energy synthesis, macromolecular synthesis, mTOR activation, and reactive oxygen balance (Sayed et al, 2019). Liu et al (2019) reported that a cofactor self-sufficient system was designed for enhanced 1,2-amino alcohols production in E. coli BL21 by overexpressing a glutamate dehydrogenase. Efficient biosynthesis of (S)-1,2-amino alcohols with respective high yields without addition of external cofactors and amino donors.…”
Section: Effects Of Co-substrates On Bhmf Synthesismentioning
confidence: 99%
“…The recombinant strains were constructed using a modified method by Liu et al [38]. Briefly, the Serratia marcescens W2.3 genome sequence was used to design primers.…”
Section: Construction Of Recombinant Strainsmentioning
confidence: 99%